The Impact of Critical Success Factors for E-Learning on Strategic Performance An applied study in a sample of the faculties for the University of Baghdad - et. al., Dr. Nada Ismaeel Jabbouri Qammach, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to test the impact of critical success factors for e-learning on the strategic performance of a sample of Baghdad University faculties. The research problem was represented by the question that states “the difficulty of using computer programs for some teachers.” The research relied on the main hypotheses represented by the hypothesis of the correlation test and another hypothesis of a simple linear regression test that emerged Including sub-hypotheses to explore and address the research problem. While the research sample consisted of (242) professors from the University of Baghdad in four selected colleges (administration and economics, sciences for girls, media, law), and the questionnaire was used as a main tool for data collection, which was prepared by the researcher based on ready-made standards, and the researcher adopted a group of Statistical methods, including (arithmetic mean, standard deviation, coefficient of variation, relative importance, correlation coefficient, regression coefficient, T-test, F-test, percentages), and data were analyzed through the use of statistical programs (AMOS V.25, SPSS V.25) The research adopted the descriptive analytical method. Among the most prominent results that have been reached is that there is a correlation and a statistically significant effect between the critical success factors for e-learning with its dimensions (information technology, the teaching staff) and the strategic performance with its dimensions (the internal operations perspective, the learning and growth perspective, the financial perspective, and the customer perspective).